Rethinking the Invisible Constitution: How Unwritten Constitutional Principles Shape Political Decision-Making - MacDonnell, Vanessa (McGill Law Journal / Revue de droit de McGill)

(untitled) (McGill Law Journal / Revue de droit de McGill, 2019)
“Unwritten” or “common law” constitutionalism has a long history in Canada. To date, the scholarship has tended to focus on the question of when, if ever, it is appropriate for courts to invoke unwritten constitutional principles. Less attention has been paid to how these principles shape political decision-making. In this paper, I suggest that focusing on the situations in which unwritten constitutional principles operate at their most visible and interventionist—to provide a warrant for courts to strike down laws or invalidate government action—emphasizes their less important, if more dramatic, applications. Rather, it is in the day-to-day application of these principles by the executive and the legislature that unwritten constitutional principles perform their most important role.